Optimalisasi Akuaponik dengan Pemanfaatan Limbah Ikan Nila sebagai Sumber Nutrisi untuk Tanaman Sayuran - Pattipeiluhu, Timothy Vito; Moesarofah, Moesarofah; Khotimah, Nabila Chusnul; Rakhma, Riza Nur; Ramadhani, Naya Fitri; Faiz, Rizky Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
Food security in rural areas remains a challenge due to limited land and agricultural technology. The KKN program in Grinting Village, Tulangan District, introduced aquaponics as an integrated system combining tilapia farming and vegetable cultivation. The community was actively involved in installation, water flow repair, fish stocking, and maintenance. A total of 20 respondents participated through training and surveys. Evaluation showed an 85% success rate with good growth of fish and vegetables, despite technical issues such as pipe leakage and water quality fluctuations. This program indicates that aquaponics can be a sustainable solution for food security with continued training and village government support.